The Meaning of the Dudu Meja Tradition in the Land of Kings: A Geographical Study - Nakul, Sukma Fira; Susilo, Singgih; Astina, I Komang (Borong Newinera Publisher, 2025)
The Dudu Meja tradition in Wakal Village is a cultural practice rooted in local customs, aiming to unite all female descendants of the Nakul clan to strengthen family bonds and pass down genealogy to future generations. This study examines: (1) The geographical analysis of the tradition’s implementation, (2) Its meaning for the people of Wakal, and (3) The values it holds for the community. A descriptive qualitative method with Spradley’s ethnographic approach was used, involving domain, taxonomic, componential, and cultural theme analysis. Data were collected through participant observation, in-depth interviews, and documentation. Key informants included the village head, the head of craftsmen, and traditional elders, while supporting informants were community members who practice the tradition. The findings reveal: (1) The geographical aspects of the tradition are shaped by the surrounding socio-cultural conditions. (2) Its meanings for the community include honoring ancestors, expressing gratitude, strengthening social ties, and preserving cultural heritage. (3) The tradition’s values include cultural values honoring ancestors, preserving heritage, and safeguarding heirlooms; social values family bonds, mutual cooperation, respect, responsibility, and consensus-building; and religious values collective prayers as an expression of gratitude and seeking Allah SWT’s blessings for a smooth implementation.